How are important career services for Islamic college students? - Moh. Khoerul Anwar; Zaen Musyrifin; Afifatuz Zakiyah (Association for Scientific Computing Electrical and Engineering(ASCEE), 2021)
The purpose of this study is to identify the importance of career services and career service delivery to Islamic college students. The implementation and importance of career services for each campus is different, depending on the direction of policy and leadership. The approach used in this research are a survey using a career service instrument that has been developed. Respondents of this study were 786 students from various departments and grades at UIN Sunan Kalijaga Yogyakarta Indonesia. The research findings indicate that 98.9% of each student needs career services in the form of adjustment to majors, development of potential and personal skills, and career preparation related to the world of work, while the implementation of career services that have been running is relatively different for each department and faculty. In the Tarbiyah and Teacher Training faculties, they get more career services with an average (103.6) such as getting great opportunities for their students to do internships before graduating, but in the ad humanities social sciences and humanities faculty with an average (89.1) they still need improvement of career services for students.